Astronomia em sala de aula: uma experiência com teatro de fantoches - Almeida, Magna Cely Cardoso de Lima (2021)
There are several discussions regarding the insertion of Astronomy contents in basic education, but we know that the existing gaps regarding teacher training, the absence of didactic materials and pedagogical resources contribute to this not being effective. In this sense, in order to contribute to overcome this gap in the practical field and expand the possibilities of methodological alternatives and instruments for teaching Physics, we bring a proposal to work Astronomy through the puppet theater. In particular, the educational product is aimed at teachers of basic education, especially teachers of high school physics to address Astronomy subjects, and consists of a dramaturgical script and indications of how to work it with their students through Puppets Theater. The research is characterized as action research and was developed in different stages, from the preparation of the material to its application at school. In general, the results show that even with the exhibition of the theater, the spectator students are unable to make a relation of the contents to the teaching of Astronomy, there is a lack of knowledge on the subject and, when they present this knowledge, they are very punctual and superficial. On the other hand, they were very receptive to the proposal, and point out the approach with the use of theater as positive.